In Vivo function of the lipid raft protein Flotillin-1 during CD8+ T cell-mediated host surveillance - Ficht, Xenia; Stolp-Rastätter, Bettina (The journal of immunology, 2019)
Flotillin-1 (Flot1) is an evolutionary conserved, ubiquitously expressed lipid raft-associated scaffolding protein. Migration of Flot1-deficient neutrophils is impaired because of a decrease in myosin II-mediated contractility. Flot1 also accumulates in the uropod of polarized T cells, suggesting an analogous role in T cell migration. In this study, we analyzed morphology and migration parameters of murine wild-type and Flot1−/− CD8+ T cells using in vitro assays and intravital two-photon microscopy of lymphoid and nonlymphoid tissues. Flot1−/− CD8+ T cells displayed significant alterations in cell shape and motility parameters in vivo but showed comparable homing to lymphoid organs and intact in vitro migration to chemokines. Furthermore, their clonal expansion and infiltration into nonlymphoid tissues during primary and secondary antiviral immune responses was comparable to wild-type CD8+ T cells. Taken together, Flot1 plays a detectable but unexpectedly minor role for CD8+ T cell behavior under physiological conditions.